Financial Literacy as a Catalyst for the Formation of Islamic Economic Morals in Students: A Case Study at SB SIKL Cheras, Malaysia - Dita Ayu Anggita Sari; Sholikah Sholikah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study was motivated by the importance of early financial literacy in shaping economic character in accordance with Islamic values, especially for migrant children in informal educational settings where character development is often neglected. The purpose of this study was to examine the role of financial literacy as a catalyst in shaping the Islamic economic character of students at SB SIKL Cheras Malaysia. The method used was a qualitative case study approach with data collection techniques through observation, in-depth interviews, and documentation, which were then analyzed using the Miles and Huberman interactive model. The results showed that the application of financial literacy through the practical “Celengan Impian” (Dream Piggy Bank) program was effective in improving students' understanding of distinguishing between needs and wants and the principles of Islamic money management. In conclusion, financial literacy has proven to be a catalyst that successfully internalizes the values of honesty, responsibility, discipline, and qona'ah (modesty) in students' daily economic behavior. This program provides a strong foundation of economic ethics for students in informal educational environments.